Efeito da pesca de arrasto do camarão-rosa sobre a dinâmica populacional de Callinectes danae e Callinectes ornatus (Crustacea, Portunidae), na Baía de Guanabara, Rio de Janeiro, Brasil - Keunecke, Karina Annes (2006)
The present work analyzed the population dynamics of Callinectes danae Smith, 1869 and Callinectes ornatus Ordway, 1863 (Crustacea, Portunidae) captured as by-catch from pink-shrimp trawlings at Guanabara Bay. Three aspects were approached: reproduction, growth and mortality. The reproductive analysis pointed out four stages of gonadal maturation for both species, corroborated by histological procedures and classified as: stage I - immature, stage II - developing, stage III - ripe and stage IV - spent. The presence of oocytes I and oocytes II in the stages ripe and spent confirmed the multiple spawning hypotheses for the species. The size at first gonadal maturity was 85.2 mm and 67.2 mm respectively for C. danae and C. ornatus. The continuous reproduction pattern was observed, however with seasonal and alternated reproductive picks in the bay. While C. danae presented reproductive picks in the autumn and in the winter, C. ornatus presented an apparent reproductive pick in the summer and probably another one in the spring. The sexual proportions diverged in C. danae significantly in females favor (3.0:1). However, to C. ornatus the proportions diverged with prevalence of males (1.2:1). This pattern indicated that possibly the females of C. danae return to the estuary after the spawning, while the ovigerous females of C. ornatus migrate to adjacent coastal areas around the bay. The growth analysis was based on indirect methods of size-frequency distributions. The growth parameters were estimated according von Bertalanffy s (1938) growth function and longevity according D Incao & Fonseca (1999). The L∞ value corresponded to the largest individual captured for each species and for each sex. For C. danae the growth x parameters were the following ones: females - L∞ = 113 mm, k = 0.005088387 and longevity = 2.48 years; males - L∞ = 120 mm, k = 0.005550913 and longevity = 2.27 years. For C. ornatus the growth parameters were: males - L∞ = 94 mm, k = 0.005372092 and longevity = 2.34 years; females - L∞ = 110 mm, k = 0.00594237 and longevity = 2.25 years. The instantaneous rate of total losses (Z ) from Ricker's (1975) catch curve associated to the natural mortality from Taylor's (1959) method showed high values of (F) mainly on the females of both species. However, for the females of C. ornatus the migration actuated in an intense way increasing the instantaneous rate of total losses. The stocks explotation rates were also high. Except for the males of C. danae, all the others were above the acceptable exploration. Besides that, 50.7% and 87.2% of females respectively from C. danae and C. ornatus were captured below the mean size at gonadal maturation. The diagnostic above suggests more effective management actions on these natural resources, not only by the responsible governmental organs, but also, by all the actors involved in the process.